Evolutive complications of abdominal trauma - Melogno, Silvio; Abella, Manuel E; Bacigaluz, Eduardo; Balboa, Oscar; Pereyra Bonasso, Jorge; Saéz, Hugo; Sálice, Mario; Voelker, Ricardo (Cirugía del Uruguay, 1981)
According to bibliographic research and the to the Iimited experience of multiple Uruguayan surgeons we have come to the conclusion that, notwithstanding the many years during which this subjet has been discussed and the diagnostic and therapeutical advances, abdominal contusions continue to pose important problems in daily practice.